Analysis about benefits of software-defined wide area network: a new alternative for WAN connectivity - Mena Diaz, Catherine Janire (2022)
This article is based on conducting research to analyze the benefits of emerging trends in communications and networking technology, such as software-defined wide area networks. Using Waterfall as a methodology, the main objective is to carry out a technical comparison at the design and configuration level, creating a virtual environment that simulates traditional and SDWAN (Software-Defined Wide Area Network) infrastructures. The results obtained verify that the benefits of SDWAN maintain business continuity, anticipate situations in which the infrastructure can act intelligently, optimize connectiv-ity while maintaining security, and provide improvements in the management of the entire infrastructure. People will be able to see the results obtained between both technologies and validate the benefits that SDWAN offers .